New perspectives in cancer drug development: computational advances with an eye to design. Issue 9 (16th July 2021) - Castelli, Matteo; Serapian, Stefano A.; Marchetti, Filippo; Triveri, Alice; Pirota, Valentina; Torielli, Luca; Collina, Simona; Doria, Filippo; Freccero, Mauro; Colombo, Giorgio
Abstract : Allosteric and cryptic pockets are emerging as promising targets to develop strategies expanding the chemical space of new drug candidates. Innovative computational methods play a key role in their discovery. Abstract : Computational chemistry has come of age in drug discovery. Indeed, most pharmaceutical development programs rely on computer-based data and results at some point. Herein, we discuss recent applications of advanced simulation techniques to difficult challenges in drug discovery. These entail the characterization of allosteric mechanisms and the identification of allosteric sites or cryptic pockets determined by protein motions, which are not immediately evident in the experimental structure of the target; the study of ligand binding mechanisms and their kinetic profiles; and the evaluation of drug–target affinities. We analyze different approaches to tackle challenging and emerging biological targets. Finally, we discuss the possible perspectives of future application of computation in drug discovery.